Burnout and Obesity in Middle and Upper Management in the Manufacturing Industry of Baja California - Macias Velasquez, Sharon Idali; Maldonado-Macías, Aide Aracely; Baez-Lopez, Yolanda Angelica; Limon-Romero, Jorge; Tlapa, Diego (IGI Global, 2019)
Globally, companies are increasingly considering the importance of mental health in workers and their relationship with productivity, which has led to increased research on work stress, which showed that there is a relationship between stress related to work and health disorders, both physical and mental. This chapter addresses the analysis of two of the main consequences that a worker can develop when having work stress: burnout syndrome, measured by the Maslach burnout inventory general survey (MBI-GS) and obesity, through the body mass index (BMI). The study was carried out in 118 people who occupy middle and upper management of the manufacturing industry of Baja California, having as objective to find the relationship that exists between the two variables, using ordinal logistic regression, as well as to characterize the sample using mean difference and hypothesis testing. From this perspective, this chapter can serve as a guide to study the behavior of variables and propose organizational development strategies aimed at reducing and preventing these problems.